2006
DOI: 10.1007/s00330-006-0487-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of primary two- and three-dimensional methods to review CT colonography

Abstract: The aim of our study was to compare primary three-dimensional (3D) and primary two-dimensional (2D) review methods for CT colonography with regard to polyp detection and perceptive errors. CT colonography studies of 77 patients were read twice by three reviewers, first with a primary 3D method and then with a primary 2D method. Mean numbers of true and false positives, patient sensitivity and specificity and perceptive errors were calculated with colonoscopy as a reference standard. A perceptive error was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…This was confirmed in a recent meta-analysis with a pooled sensitivity of 83% for studies with primary 3-D imaging compared to 64% for primary 2-D imaging 21. However, some studies have found a primary 2-D approach to be comparable to a primary 3-D endoluminal analysis 33 34. Data suggest that computer-aided detection (CAD) systems might be helpful for evaluating CTC images 35 36…”
Section: Protocols For Ctc Scanningmentioning
confidence: 79%
“…This was confirmed in a recent meta-analysis with a pooled sensitivity of 83% for studies with primary 3-D imaging compared to 64% for primary 2-D imaging 21. However, some studies have found a primary 2-D approach to be comparable to a primary 3-D endoluminal analysis 33 34. Data suggest that computer-aided detection (CAD) systems might be helpful for evaluating CTC images 35 36…”
Section: Protocols For Ctc Scanningmentioning
confidence: 79%
“…Although the discussion as to whether to read the data in 2D or 3D is still not settled, a (slight) superiority in terms of polyp detection with 3D is reported by some studies [37,38]. Since the reported sensitivities of a primary 2D paradigm tend to be lower, CAD may have a larger additional value when used in a 2D reading protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Once the CT volume has been acquired (preferably with low-dose, thinsection multislice imaging) [1,2], the native images can be directly viewed on the monitor of the reporting workstation (2D technique) or processed on dedicated workstations for intraluminal viewing (virtual endoscopic or 3D technique). Many authors agree that the diagnostic efficiency of CT colonography is improved by using the two visualisation techniques in combination [2,3]. In Italy, CT colonography has been in clinical use for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Per far questo sono requisiti essenziali la adeguata pulizia intestinale e la distensione del colon ottenute con metodi specifici. Una volta condotta l'acquisizione del volume TC (preferibilmente con metodica multistrato con bassa dose e spessori di strato sottili) [1,2] [2,3]. In Italia la CV è in uso clinico da ormai alcuni anni.…”
Section: Introduzioneunclassified